Administration of nOPV2 Polio National Immunization Days (PIN) for Children Aged 0–7 Years as a Preventive Measure Against Poliomyelitis: nOPV2 Polio PIN for Children as Polio Prevention - Aca Tuharea; Harianti Fajar (CV. Paperhome Indonesia, 2025)
Poliomyelitis (polio) is a highly infectious disease caused by the poliovirus and can lead to permanent paralysis. To address outbreaks of type 2 poliovirus, the Indonesian government implemented the National Immunization Week (PIN) using the novel Oral Polio Vaccine type 2 (nOPV2). This initiative aims to increase polio immunization coverage, particularly among children aged 0–7 years, who are most vulnerable to the disease. This activity was conducted in two sub-districts—Karang Panjang and Amantelu—through school visits and local health posts (posyandu). Each vaccinated child’s immunization card was updated, and families received counseling regarding the importance of polio vaccination. The campaign in the working area of Karpan Health Center, Ambon, reached 1,204 children, achieving 77.8% coverage. Community participation, especially among parents, was enthusiastic. Future efforts are expected to increase coverage to 100% through continued public engagement and education.